Design and Finite Element Analysis of Flexspline for Different Tooth Profile Harmonic Drive - Huang Wei; Wang Jiaxu; Xiao Ke; Li Junyang (Jixie chuandong)
The tooth profile curve of double-arc common-tangent tooth profile harmonic reducer is established and the conjugate tooth profile fitting analysis for double-arc common-tangent tooth profile designed by enveloping theory is carried out. By using the ANSYS,the involute tooth profile and double-arc common-tangent tooth profile harmonic reducers are analyzed and compared,and the radial and tangential deformation of tooth profile under the condition of no load and loading of the two teeth profiles are analyzed. The results show that,the deformation of tooth profile of the double circular arc and involute tooth profile under the condition of no load is the same,after loading,the deformation of the double circular arc is less than that of the involute tooth profile and has larger bearing capability.